CUT, do classismo à cooperação de classes: a CUT entre pressões, determinações e escolhas - Sacramento, Ednaldo Mendes (2014)
This paper presents the results of a survey on the changes that will render in the Central Única dos Trabalhadores – CUT, from the beginning of the decade of 1990, which transformed the character of this organization from a central Union classist to a collaborative entity classes. The trajectory of this organization was marked by intense debates and disputes, of the projects, however mark two times when these disputes were decisive: in 1983, when it was founded, with the victory of currents that defended a unionism classist, independent in relation to the State and based on the direct action of the workers, from the perspective of socialism. The other time was in the early 1990, when labor majority in the current joint CUT gradually was abandoning marxist references, passing defending proposals to overcome crises capitalist system and the participation of the Central in conciliation forums of class. The main objective of this research is to contribute to the explanation of these changes, from the analysis of the dynamics of class struggle, the internal organization of the Central dispute of political projects in its interior, as well as social places that the leaders of the CUT began to occupy. Sought to develop the work trying to answer the question on the existence, or not, of possibilities of choices by the direction of the institution, on the difficulties created for workers by the actions of the ruling class, attentive to the idea of reciprocal determinations. The approach to the Central Única dos Trabalhadores was a collective organizer, in a gramscian perspective. The central hypothesis is that the process of bureaucratization and the new functions occupied by cutistas leaders had decisive weight to changes.